Intimations of everyday life. - Galloway, Anne (Cultural Studies)
Ubiquitous computing seeks to embed computers into our everyday lives in such ways as to render them invisible and allow them to be taken for granted, while social and cultural theories of everyday life have always been interested in rendering the invisible visible and exposing the mundane. Despite these related concerns, social and cultural studies have been almost entirely absent in discussions of the design of ubiquitous technologies. This essay seeks to introduce researchers in both fields to each other, and begin to explore the ways in which collaboration might proceed. By exploring mobile and ubiquitous technologies currently being used to augment our experiences of the city, this paper investigates notions of sociality, spatialization and temporalization as central to our experiences of everyday life, and therefore of interest to the design of ubiquitous computing.